Glucocorticoid Therapy in COVID-19 - Amati, Francesco; Tonutti, Antonio; Huston, John; Dela Cruz, Charles S. (Seminars in Respiratory and Critical Care Medicine, 2023)
Coronavirus disease 2019 (COVID-19) pneumonia caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has resulted in significant mortality in pandemic proportions. Inflammation in response to the infection contributes to the pathogenesis of pneumonia. This review will discuss prior studies on the use of glucocorticoids to treat respiratory infections, the rationale for the use glucocorticoids in COVID-19, and review of existing data. We will also highlight outstanding research questions for future studies.
Keywords: glucocorticoid; treatment; COVID-19